2009
DOI: 10.1088/0957-4484/20/6/065401
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopy of shallow InAs/InP quantum wire nanostructures

Abstract: A comprehensive investigation of the optical properties of InAs/InP(001) quantum wires (QWrs) and their parent quantum well system formed by the deposition of 4 ML (monolayers) of InAs on InP is carried out by means of temperature dependent photoluminescence (PL) and Fourier transform infrared spectroscopy. Unusual two-branch switching of the excitonic PL band maxima is revealed in the temperature dependence for both wires and wells. This is interpreted in terms of the thermal activation of excitonic ground st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 43 publications
1
1
0
2
Order By: Relevance
“…The temperature dependence of the PL peak energy for this high excitation case more closely follows equation (6). The S-shaped dependence seen in the low-intensity PL spectra of samples 1 and 2 can be related to the existence of two separate PL peaks with different temperature dependences, as in figure 5(b) [23,24]. The higher energy peak dominates at low temperatures and remains in the PL spectra at high temperatures.…”
Section: (B) and (D)supporting
confidence: 61%
“…The temperature dependence of the PL peak energy for this high excitation case more closely follows equation (6). The S-shaped dependence seen in the low-intensity PL spectra of samples 1 and 2 can be related to the existence of two separate PL peaks with different temperature dependences, as in figure 5(b) [23,24]. The higher energy peak dominates at low temperatures and remains in the PL spectra at high temperatures.…”
Section: (B) and (D)supporting
confidence: 61%
“…In [3], core-shell nanowires were experimentally obtained, and it was shown that the cross-sectional area is in the shape of a hexagon. Optical properties of InAs/InP-based quantum wires were studied by photoluminesce spectroscopy [4]. e optical properties of core-multishell nanowires based on InP/InAs/InP were experimentally studied in [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…A literatura científica tem reportado a formação de fios quânticos, ou NWs (Nanowires), para o crescimento de InAs sobre InP [40], [41], [42]. Nas imagens de AFM da figura 2.5 é possível observarmos a formação de NWs à medida que o tempo de crescimento da camada de InAs aumenta de 6 para 12 s. O processo de crescimento inicialmente é regido por SK, porém a formação dos pontos acontece de forma seletiva, ou seja, sobre eixos que provavelmente representam a orientação cristalina do substrato, visível nas três imagens de AFM.…”
Section: Pontos Quânticos De Inas Crescidos Sobre Inpunclassified
“…A figura 2.6(b) mostra as dimensões dos pontos também em função do tempo de crescimento da camada de InAs; novamente, como presumido anteriormente, o diâmetro e a altura aumentam na mesma razão de aspecto (proporção entre diâmetro e altura) à medida que o tempo aumenta de 6 para 8 s; no entanto, quando o tempo aumenta para 12 s, o diâmetro aumenta e a altura diminui, aumentando a razão de aspecto, indício de formação de NWs. Quando formados, NWs apresentam razão de aspecto (comprimento por diâmetro) da ordem de 40 ou mais [43], [42]. O desvio padrão da altura e diâmetro dos pontos variou de 1-3 e 8-40 nm, respectivamente.…”
Section: Pontos Quânticos De Inas Crescidos Sobre Inpunclassified